The effectiveness of counseling by activists through social media tiktok in preventing sexual harassment of women : . - nabila elvana; Retno puji Rahayu; Dr. Wahyunengsih M.pd (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
The purpose of our study is to find out how much influence and effective counseling through social media tiktok in preventing sexual harassment to Women. Tiktok is a popular social media application in Indonesia and is used as entertainment only and as a means of learning and disseminating information. Many content creators from their respective fields start to carry out their roles through this application, one of which is extension. There are many extensions who spread their counseling by making tiktok videos by taking issues that are being crowded on tiktok. Like about sexual harassment in women that currently occurs very often. The object of our research is the followers of extension content creators on the tiktok application . We wanted to find out if there was any influence from watching the extension content creator video to his followers. This type of research uses qualitative methods with a phenomenological approach, data sourced from primary data with questionnaire techniques involving 63 respondents. From the results of the research conducted showed that by watching counseling videos from tiktok made them affected and changed their perspective regarding the things discussed in the video itself. One of the things discussed in the video is the sexual harassment of